Influence of metal turning assisted with high density current pulses on surface hardness in an AISI/SAE 1045 steel - Montilla Montaña, Carlos Alberto; Jaramillo Blandón, Jeison Steven; Rodríguez Valencia, Andrés Felipe (Scientia et Technica, 2019)
Within the family of electrically assisted forming processes EAF, the hybrid process of turning assisted in-situ with electropulses, is being studied to determine the influence of electropulses on machining power, surface finish and macro hardness. Applying DOE techniques, the present research work focuses on studying the response of macro hardness in an AISI / SAE 1045 steel under an electrically assisted turning process, considering different factors. The results obtained from the Analysis of Variance ANOVA show that the feed has an influence on the surface hardness of the material. Likewise, the interaction between the factors pulse frequency and pulse width of the electrically assisted turning process shows an impact on the surface hardness of AISI / SAE 1045 steel. The triple interaction between feed, pulse frequency and pulse width, may have an impact on the response characteristic under study.